Analisis kadar protein udang vaname (Litopenaeus vannamei) oleh pengaruh iradiasi gamma (Cesium-137) - Mahyuddin, Rahmawati; Fuadi, Nurul; Jumardin, Jumardin; Zelviani, Sri; Isradianti, Dwi Febri; Hidayat, Serli Hatul (Teknosains: Media Informasi Sains dan Teknologi, 2025)
Vannamei shrimp (Litopenaeus vannamei) is a fishery product that is prone to spoilage due to microbes during storage, hence finding solutions to extend its shelf life is necessary. One effective technique to inhibit microbial growth is non-thermal preservation using gamma irradiation. However, the irradiation dose must be carefully considered to avoid reducing the protein content in the shrimp. This study aims to determine the effect of gamma irradiation dose (Cesium-137) on the protein content of vannamei shrimp. The research method used Cesium-137 irradiation with varying doses of 0 mGy (control), 10 mGy (0.4 hours), 30 mGy (0.9 hours), and 50 mGy (1.3 hours). Sample irradiation was performed at a constant distance of 100 cm. Protein content was determined using Uv-Vis spectrophotometry, referencing standard curves and Bovine Serum Albumin (BSA) solution concentrations. The results showed protein contents of 0.146%, 0.180%, 0.268%, and 0.316%, respectively. These results indicate that protein content has a significant relationship with the radiation dose and irradiation time of Cesium-137. This study suggests that gamma irradiation can be used to extend the shelf life of vannamei shrimp without significantly reducing protein content.